B-almost distributive fuzzy lattice - Assaye, Berhanu; Alemneh, Mihret; Tefera, Gerima (Bulletin of the Section of Logic, 2018)
The paper introduces the concept of B-Almost distributive fuzzy lattice (BADFL) in terms of its principal ideal fuzzy lattice. Necessary and sufficient conditions for an ADFL to become a B-ADFL are investigated. We also prove the equivalency of B-algebra and B-fuzzy algebra. In addition, we extend PSADL to PSADFL and prove that B-ADFL implies PSADFL.